(untitled) (Research, Society and Development, 2022)
Objective: To develop and validate a form to assess the adherence of basic health units to tuberculosis control measures. Methodology: This is a methodological study to develop a questionnaire based on national and international literature on the subject. Content and semantic validation took place through the use of the Content Validity Index (CVI) and the binomial test, with the voluntary participation of 22 specialists and 12 health professionals recruited from 6 basic health units in district IV of the city of Recife - PE included in the study. Result: The questionnaire obtained satisfactory CVI values, mostly greater than or equal to 0.80, but some items did not reach the minimum CVI value, but were considered significant due to approval by the binomial test, being greater than the reference of 0 .05, with the exception of one item that was withdrawn. All the judges’ suggestions were accepted in order to make the items more cohesive and understandable. Conclusion: Thus, the instrument is considered valid in content and semantics, with three domains: administrative activities, environmental control actions and individual protection measures, and 34 items in its final version.